Finding Kindness - Underwood, Deborah; Chan, Irene (Illustrator) (New York : Godwin Books, Henry Holt and Company, 2019)
Rhyming text celebrates kindness in all its many forms, from sending a heartfelt card to lending a hand with yardwork.
Keywords: Kindness -- Fiction; Conduct of life -- Fiction; Stories in rhyme